Analysis of Employee Performance at the Bahu Subdistrict Office: Study on Aspects of Quality, Quantity, Timeliness, Effectiveness and Work Independence - Vanessa Rambulangi; Jony. R.E Tampi; Femmy M. G. Tulusan (Newinera Publisher, 2024)
The sub-district government is a work unit that directly serves the community. The inability of employees to carry out each work program is a reflection of their achievements, performance and service. This research was conducted to determine the performance of employees at the Bahu Village Office, Malalayang District, Manado City. The research design used is qualitative. The research findings show that the performance of employees in the Shoulder sub-district office is generally good in terms of work quality, work quantity, effectiveness, punctuality and work independence. This success cannot be separated from the quality of the employees and the system that has been developed through applicable regulations, the leadership style of the sub-district head and the work culture that has been developed in the Bahu sub-district office. There were also several complaints about employee discipline that still needed to be improved. Therefore, training is needed to increase the capability of officers in serving the community and mastering information technology. In order to increase the quantity of work by employees, it is recommended to create applications for community service. To optimize service time, it is necessary to increase work discipline and to measure performance through monthly or quarterly reports by superiors to sub-district employees so that employee work independence can be seen.